Social media in the purchasing of knowledge-intensive business services - Ojanaho, Tiia (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The purpose of this thesis was to understand how industrial buyers utilize social media in the purchasing of knowledge-intensive business services. By combining theories from past research a theoretical framework was formed to visualize the role of the social media at the different stages of the purchasing process. The subject was approached from the industrial buyers’ perspective instead of the knowledge-intensive business firm. The research was conducted using two qualitative research methods: interviews and netnography. The selected interviewees have been involved in the decision-making unit for purchasing knowledge-intensive business services. Additionally all of them are using various social media. Based on the interviews social media is used merely to support decision-making. Some of the interviewees had also shared their own experiences about the service and collaboration with the service provider with other social media users. Based on the interviews two social media were chosen for closer examination. The findings from netnography support the results from the interviews. The outcome of knowledgeintensive business services is dependable of the professionals. Therefore the information is used during decision-making process to confirm the formed image of the service, and the professionals of the service provider. Information obtained from social media complements information provided by the supplier. Even though the interviewees had not themselves used social media to find information about the service during search process, finding from netnography suggest it to exist. Industrial buyers ask other users’ opinions and experience about the services, and receive recommendations to them. Some recommendations are given publicly, but more discreet information is shared in private conversations. Observations in social media show that industrial buyers might be exposed to triggers to promote problem recognition as well. Companies share news and successful customer cases through their social media profiles, which might affect the industrial buyers, but to confirm this requires further research. The industrial buyers’ use of social media during different purchasing processes of knowledgeintensive business services can be conceptualize based on the findings. This helps companies to create right content to their social media pages, and encourage professionals to develop their networks in social media.